Development of Technology Integrated PJBL Based LKPD to Improve Student Learning Outcomes in Elementary School Mathematics Subjects - Aulia, Syarifah; Ali, Muhamad; Fahrurrozi, Muh. (IJE : Interdisciplinary Journal of Education, 2025)
Development of LKPD based on integrated PJBL Technology to improve student learning outcomes in elementary school mathematics subjects in grade V SDN 01 Terara using the ADDIE model. This research aims to develop PJBL-based LKPD that is integrated with technology by achieving the level of validity in the development process and the effectiveness of the developed LKPD. The data collected through observation and dissemination of questionnaires to expert experts and user response questionnaires, namely teachers and students. The quality of LKPD is measured based on two main aspects, namely the effectiveness of a product, and validity. The feasibility of the product was obtained through the evaluation of material experts, with a magnitude of 60%, a linguist's assessment of 70%, and a technologist's assessment of 63%. LKPD products based on PJBL integrated technology are said to be effective on the reciprocity of users by teachers by 71% and product users by students by 70.14%. Based on the results of the posttest and performance, the technology-integrated PJBL-based LKPD was also declared effective in improving student learning outcomes in mathematics subjects. Thus, it can be concluded that the PJBL-based LKPD product integrated with the technology developed is effective, and valid and suitable for use.